A review of the determination of organic compounds in Bayer process liquors - Power, G.; Loh, J.; Wajon, J.; Busetti, Francesco; Joll, Cynthia (Elsevier BV, 2011)
Bayer process liquors present a difficult and complex matrix to the analytical chemist, and the history of the application of modern analytical techniques to this problem is a case study in innovation. All Bayer process liquors contain organic compounds, in amounts varying from traces to several grams per litre. The total organic carbon content of Bayer liquors may be less than 5 g/L up to as much as 40 g/L. The presence of these organic impurities is of concern to Bayer technologists because they can have significant impacts on the economics of the process and the quality of the product. This review examines the history and current state-of-the-art of the analysis of organics in Bayer process liquors, and provides guidance on the applicable techniques matched to a comprehensive list of the compounds most likely to be present.